The history of the study of the formation of the ethnic territory of the Kazakh people of the XV century – the beginning of the XVIII century (until the 20th century of the twentieth century) (Journal of history, 2018)
The article is devoted to the first period of the history of the study of the thesis «History of the formation of the ethnic territory of the Kazakh people (XV century – the beginning of the XVIII century)». The author tries to find out the territorial habitats of the tribes of the Kazakh people by analyzing the materials in the historiographical sources of the mid-18th century up to the twenties of the XX century. In the course of the research work historical, logical, systemic methods of historiographical research were used, the sources studied were analyzed by the time of their publication, beginning with the earliest. Thus, were made a historiographic analysis of the works of V.V. Tevkelev, P. Rychkov, Ya.P. Gaverdovski, A.I. Levshin, Sh.Sh. Valihanov, A.N. Aristov, Sh. Құdaibirdiuly, M. Tynyshpaev. In conclusion, the author especially highlights the works of Ya.P. Gaverdovski, A.I. Levshin, Sh.Sh. Valikhanov and M. Tynyshpaev, where the most detailed descriptions of the territorial habitat of almost all Kazakh families and tribes are given.